2014
DOI: 10.5455/medarh.2014.68.335-338
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Osteoporosis in Patients with Urolithiasis

Abstract: Introduction.Clinical researches have shown an increased bone disintegration and lower bone mass in patients with calcium urolithiasis.Goal.The goal of our research was to establish the incidence of osteoporosis in adult patients with calcium urolithiasis, on the basis of measuring mineral bone density, using DEXA method, with a special reflection on age subgroups.Material and methods.Clinical research was prospective and it was implemented at the University Clinical Center of Banja Luka, at the Clinic for End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Bijelic et al [53] found an increased risk of incident osteoporosis (7.5 vs. 0.8 %) in patients with renal stones compared to controls. On the contrary, Melton et al [4] found contrasting findings on incident fractures in patients with urolithiasis compared with the expected number of fractures, since patients with kidney stones experienced a higher rate of vertebral, but lower of hip fractures than those expected.…”
Section: Descriptive Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…Bijelic et al [53] found an increased risk of incident osteoporosis (7.5 vs. 0.8 %) in patients with renal stones compared to controls. On the contrary, Melton et al [4] found contrasting findings on incident fractures in patients with urolithiasis compared with the expected number of fractures, since patients with kidney stones experienced a higher rate of vertebral, but lower of hip fractures than those expected.…”
Section: Descriptive Findingsmentioning
confidence: 97%
“…Two longitudinal studies [4,53] were summarized as descriptive findings. Bijelic et al [53] found an increased risk of incident osteoporosis (7.5 vs. 0.8 %) in patients with renal stones compared to controls.…”
Section: Descriptive Findingsmentioning
confidence: 99%
“…The use of thiazides is not always sufficient, as it has been demonstrated that a high percentage of patients with recurrent renal calcium stones have an osteopenia/osteoporosis [20,21,22] that could benefit from treatment with an anti-reabsorption drug. The bisphosphonates are a group of therapeutic drugs widely used in the treatment of osteoporosis [23], although they are not free of adverse effects, one of the most severe being osteonecrosis of the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…9 It is well known that patients with hypercalciuria and fasting hypercalciuria have more risk of bone mineral density loss, 13 and that calcium renal stones and osteopenia/osteoporosis are two related and reciprocal diseases. 14 The role of urinary calcium in the physiology of stones is very important, due to the main metabolic risk factor found in patients with lithiasis. 9 The study of calciuria is recommended in women with osteoporosis and osteoporotic fracture.…”
Section: Calciuria In Postmenopausal Women With Fracturementioning
confidence: 99%